PERJUANGAN KEWISA KOTEN DI LEWOKLUOK FLORES TIMUR MELAWAN BELANDA TAHUN 1905 - Utomo, Susilo Setyo; Djakariah, Djakariah; Tukan, Joanetta M. (Jurnal Penelitian Pendidikan Sejarah UHO, 2020)
ABSTRACT: This study aims to reveal (1) the causes of the struggle of the Lewokluok people against the Netherlands in 1905, (2) the process of the struggle of the Lewokluok people against the Dutch in 1905, (3) the impact of the struggle on the Lewokluok community. The location in this study was in Lewokluok Village, Demon Pagong District, East Flores Regency. Sources of data used are written sources and oral sources. Data in this study were collected by interview, observation, document study. The research procedure uses historical research methods which include data collection (heuristics), historical criticism, interpretation and history writing (historiography). The results showed that the factor causing the struggle of the Lewokluok people against the Netherlands in 1905 was the appointment of King Louis de Rosari to replace King Don Lorenzo who was accused of killing by the Dutch. This was not approved by the people of Lewokluok. The process of the struggle of the Lewokluok people against the Netherlands in 1905 was as follows (1) the Dutch troops burned all the gardens belonging to the Lewokluok people, (2) the Lewokluok people under the leadership of Kewisa Koten and their aides tried to defend themselves behind the bushes, trying to carry out attacks reply. However, their struggle was finally broken by the Dutch troops. (3) Kewisa Koten and other traditional elders were exiled outside the area. The impact of the struggle of the Lewokluok people against the Netherlands in 1905 was: (a) Four indigenous elders were exiled. (b) Naya Lein was killed by Dutch troops. (c) Kewisa Koten was exiled to Nusa Kambangan. (d) The people of the Lewokluok village and the traditional house (Koke) were moved to Kampung Bama. (e) The property of the inhabitants of the village of Lewokluok was taken and burned by the Dutch troops. (f) Many Lewokluok people died. (g) The Dutch increasingly interfered in the affairs of the people of the kingdom of Larantuka. (h) The Netherlands forced the people of Lewokluok to submit to the Dutch command to pay taxes.